PENERAPAN SOFTWARE ATLAS DAN KOMPETENSI AUDITOR TERHADAP KUALITAS AUDIT DENGAN ETIKA AUDITOR SEBAGAI VARIABEL MODERASI - Nugrahaningtyas, Amiradewi Febrina; Priyastiwi, Priyastiwi (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2024)
This study aims to determine the application of Audit Tools and Linked Archive System (ATLAS), auditor competence on the quality of audit results with auditor professional ethics as a moderating variable in public accounting firms in the city of Yogyakarta. The research method used is a quantitative method with sampling techniques carried out by purposive sampling method which is distributed to Yogyakarta city public accountants listed in the Directory of the Indonesian Institute of Public Accountants as many as 15 KAP. Data analysis technique using Structural Equation Modeling – Partial Least Square (SEM PLS). Based on the results of the study, results were obtained that showed that the application of ATLAS and auditor competence affected the quality of audit results. Meanwhile, auditor professional ethics cannot moderate the relationship between the application of ATLAS to audits and the relationship between auditor competence to the quality of audit results.